2-D analytical modeling of the electrical characteristics of dual-material double-gate TFETs with a SiO2/HfO2 stacked gate-oxide structure - Kumar S.; Goel E.; Singh K.; Singh B.; Singh P.K.; Baral K.; Jit S. (My University, 2025)
A physics-based 2-D analytical model for surface potential, electric field, drain current, subthreshold swing (SS) and threshold voltage of dual-material (DM) double-gate tunnel FETs (DG TFETs) with SiO2/HfO2 stacked gate-oxide structure has been developed in this paper. The parabolic-approximationtechnique, with suitable boundary conditions, has been used to solve Poisson's equation in the channel region. Channel potential model is used to develop electric field expression. The drain current expression is extracted by analytically integrating the band-to-band tunneling generation rate over the channel thickness. Threshold voltage has been extracted by maximum transconductance method. The proposed model also demonstrates that the proper choice of work function for both the latterly contacting gate electrode (near the source and drain) materials which can give better results in terms of input-output characteristics, SS, and ION/IOFF than the conventional TFET devices. Although the proposed model has been primarily developed for Si-channel-based DM DG TFET devices, however, the model has also been shown to be applicable for other materials like SiGe (indirect bandgap) and InAs channel-based TFET structures. The results of the proposed model have been validated against the TCAD simulation results obtained by using SILVACO ATLAS device simulation software. © 1963-2012 IEEE.